2010
DOI: 10.1111/j.1365-313x.2009.04098.x
|View full text |Cite
|
Sign up to set email alerts
|

Early transcriptomic events in microdissected Arabidopsis nematode-induced giant cells

Abstract: Summary Root‐knot nematodes differentiate highly specialized feeding cells in roots (giant cells, GCs), through poorly characterized mechanisms that include extensive transcriptional changes. While global transcriptome analyses have used galls, which are complex root structures that include GCs and surrounding tissues, no global gene expression changes specific to GCs have been described. We report on the differential transcriptome of GCs versus root vascular cells, induced in Arabidopsis by Meloidogyne javani… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

20
308
0
1

Year Published

2012
2012
2022
2022

Publication Types

Select...
3
3
1

Relationship

1
6

Authors

Journals

citations
Cited by 209 publications
(329 citation statements)
references
References 86 publications
20
308
0
1
Order By: Relevance
“…However, throughout the assay, an increase in expression was observed, and 79% of the genes were upregulated at 9 DAI. These results agree with the expression profiles reported during root-knot nematode infection in Arachis (Guimarães et al 2010;Tirumalaraju et al 2011) and other plants, such as rice (Kyndt et al 2012), Arabidopsis (Jammes et al 2005;Barcala et al 2010), tomato (Portillo et al 2013) and cowpea (Das et al 2010). These studies reported gene repression or constant expression at early stages of nematode-plant interaction, followed by a trend towards an increasing number of upregulated genes in both compatible and incompatible interactions.…”
Section: Gene Expression Profilessupporting
confidence: 81%
See 1 more Smart Citation
“…However, throughout the assay, an increase in expression was observed, and 79% of the genes were upregulated at 9 DAI. These results agree with the expression profiles reported during root-knot nematode infection in Arachis (Guimarães et al 2010;Tirumalaraju et al 2011) and other plants, such as rice (Kyndt et al 2012), Arabidopsis (Jammes et al 2005;Barcala et al 2010), tomato (Portillo et al 2013) and cowpea (Das et al 2010). These studies reported gene repression or constant expression at early stages of nematode-plant interaction, followed by a trend towards an increasing number of upregulated genes in both compatible and incompatible interactions.…”
Section: Gene Expression Profilessupporting
confidence: 81%
“…In parallel to auxins, cytokinins also have been shown to play an important role in root-knot nematode gall formation, with high levels of expression induced in the early stages of plantparasite interaction (Goverse et al 2000;Barcala et al 2010). Cytokinin dehydrogenase (CKX) expression is induced by cytokinins, representing a negative feedback system, in which the accumulation of cytokinin induces its own catabolism, controlling the levels of the hormone in the cell .…”
Section: Hormonal Balancementioning
confidence: 99%
“…However, genome-wide profiling studies of different plant hosts during this post-induction/early nutrient acquisition 8 stage of infestation appear to support the general consensus for a suppression or absence of host defense signaling in giant cells induced by root-knot nematodes. In a microarray analysis of giant cells isolated from Arabidopsis roots at 3 days, genes included within the biotic stress functional category were in a general trend toward reduced transcript accumulation when compared to vascular tissues of non-infested root sections [24]. Similar results were also observed in giant cells isolated from infected tomato roots at 3 days and compared to vascular cells from non-infested roots [21].…”
Section: Local Host Responses To Root-knot Nematode Infestationsupporting
confidence: 53%
“…Due to the fact that infestation sites are generally already well developed by 7 days, it is difficult to distinguish whether changes at these stages are a local response to pathogen invasion, a systemic response to the infestation itself or an endogenous response to altered plant metabolism. Within the giant cells themselves, the general trend is clearer than that for surrounding tissues and the majority of differentially expressed defense-related genes were found to be down-regulated throughout the nutrient acquisition stage [21,24].…”
Section: Local Host Responses To Root-knot Nematode Infestationmentioning
confidence: 94%
See 1 more Smart Citation